Value Addition in Flower Crops Through Production Of Potpourri - Safeena , SA; Thangam , M (Bangladesh Journal of Botany, 2023)
Consumer acceptance of naturally dried decorative materials is fairly good. Left-over floriculture produce can be turned into value-added eco-friendly products like Potpourri. Experiments were conducted to evaluate the ability of dried-petals of roses to obtain and retain diverse colour shades for production of potpourri. Dip-dyeing method was employed for tinting of dried rose-petals for potpourri-production. Results have shown that potpourri tinted with edible-dyes and mixed with essential-oils could be commercially produced on a large scale for greater consumer acceptability. Present study confirmed that tinting of dried rose-petals with edible-dyes can enhance the value of potpourri by providing a hue of colours and it helps farmers in earning more returns. Potpourri is a 100 per cent natural product and can be effectively used to combat the detrimental effects of synthetic-fragrances or artificial air-freshners. Bangladesh J. Bot. 52(1): 87-96, 2023 (March)